The evaluation of formulations for the preparation of new formula pellets - Gajdziok, Jan; Bernatoniene, Jurga; Muselík, Jan; Masteiková, Ruta; Dvořáčková, Kateřina; Petkeviciute, Zivile; Lazauskas, Robertas; Kalveniene, Zenona; Bernatoniene, Rūta (Pharmaceutical development and technology, 2011)
The aim of the study was to prepare pellets of maidenhair tree (Ginkgo biloba), motherwort (Leonurus cardiaca) and hawthorn (Crataegus monogyna) dry extracts by extrusion/spheronization method. The critical step of this process was the amount of added wetting liquid (water-ethanolic mixture) and the amount of extract in the formulation. The samples of pellets containing 30-50% of extracts were formulated: Pellets contained extracts of Ginkgo, Crataegi and Leonuri. The last sample was aimed at the formulation of pellets with the content of 30% of the mixture of Ginkgo, Leonuri and Crataegi extracts in a ratio of 1:5:6. The remainder of the solid compounds in all formulations was microcrystalline cellulose (Avicel® PH-101). It was not possible to find a way to adequately wet the formulations with the content of extracts higher than 30% because of the unsuitable properties of all three extracts used. On the basis of the experiments, pellets with mixtures of all three previously used extracts were prepared. These pellets showed perfect physico-mechanical properties: Hardness (10.00 ± 2.24 N), friability (0.06%), repose angle (20.99 ± 0.41°), flowability (6.97 ± 0.29 s/100g of pellets), sphericity (0.81 ± 0.05), compressibility index (4.65%), intraparticular porosity (0.09%) and interparticular porosity (45.11%), which predetermine them to other testing and usage (feeling into capsules, tableting, coating etc.).
Keywords: Capsules; poréznost; Leonurus; Wetting Agents; tobolky; Porosity; chemické jevy; příprava léků; srdečník; Cellulose; rostlinné extrakty; Chemical Phenomena; celulosa; tvrdost; Hardness; zvlhčující látky; Plant Extracts; Ginkgo biloba; pomocné látky; Excipients; Drug Compounding; Crataegus